A influência do Banco Mundial sobre as reformas da previdência social brasileira : causas e consequências - Magioni, Mirella Januário (2013)
This paper aims to analyze the influence of the World Bank in the Brazilian Social Security reform, identifying how this influence was important to shape this policy. For that, the method we used was the documentary research. Data were collected from the documents published by the World Bank in the 1990's and the 2000's, all related to the Social Security reform in Brazil and also the documents which deal with the World Bank's position on the social policies for developing countries. For the document analysis, it were used criteria which included the approach path of the World Bank to the Social Security policy, as well as the changes in this path caused by the new requirements imposed by the social and economic dynamics. We concluded the influence of World Bank in the Brazilian Social Security reforms only makes sense if we cross Brazil's singular trajectory in this process with all the identified changes in the path of the Bank, which needed to choose new instruments and adopt a new position. Therefore, we realized this influence was built as required by the social and economic limitations of Brazil to reform Social Security, which in turn requested from the World Bank a position based on consensus building, which admitted a more gradually paced reform in the country.